The Library of Congress View on Its Relation to the ALA MARC Advisory Committee - Avram, Henriette D. (Information Technology and Libraries, 1974)
This paper is a statement of the Library of Congress' recommendation that a MARC advisory committee be appointed within the present structure of the RTSD/ISAD/RASD Committee on Representation in Machine-Readable Form of Bibliographic Information (MARBI) and describes the Library's proposed relation to such a committee. The proposals and recommendations suggested were adopted by the MARBI Committee during its deliberations at ALA Midwinter, January 1974, and are now in effect.